La colonie de St. Domingue ne pouvant parvenir à sa splendeur passée qu'en ranimant l'agriculture ... j'ordonne qui suit . - Toussaint Louverture, 1743-1803 (1798)
Thirteen emergency orders issued by Toussiant Louverture in an effort to return the colony to its former orderly existence prior to the invasion by the English.